2020
DOI: 10.3390/ijms21239082
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanopeanuts as Prospective Support for Cisplatin in Glioblastoma Nano-Chemo-Radiotherapy

Abstract: Herein, we propose newly designed and synthesized gold nanopeanuts (Au NPes) as supports for cisplatin (cPt) immobilization, dedicated to combined glioblastoma nano-chemo-radiotherapy. Au NPes offer a large active surface, which can be used for drugs immobilization. Transmission electron microscopy (TEM) revealed that the size of the synthesized Au NPes along the longitudinal axis is ~60 nm, while along the transverse axis ~20 nm. Raman, thermogravimetric analysis (TGA) and differential scanning calorimetry (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Studies have shown that, after connecting cisplatin with AuNPs, the resulted cPt@AuNPs combined with RT could lead to 50% death rate of U251 cells in vitro. 70 Hsiang-Kuang Tony Liang et al found that carboplatin-loaded hydrogel enabled sustained drug release and facilitated the synergistic effect with RT. 71 As a good biocompatible material, hydrogel remained stable for almost 5 weeks.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…Studies have shown that, after connecting cisplatin with AuNPs, the resulted cPt@AuNPs combined with RT could lead to 50% death rate of U251 cells in vitro. 70 Hsiang-Kuang Tony Liang et al found that carboplatin-loaded hydrogel enabled sustained drug release and facilitated the synergistic effect with RT. 71 As a good biocompatible material, hydrogel remained stable for almost 5 weeks.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…Finally, gold nanopeanuts (AuNPes), which are thermally stable up to 110 °C and present favorable drug-immobilizing properties (e.g., cisplatin), may be valuable in concurrent chemo- and radiotherapy. The characteristic shape of the nanoconstructs, which resembles a “peanut”, increases the surface area for the immobilization of chemotherapeutics enabling the delivery of a larger cargo of drugs [ 74 ].…”
Section: Metal-based Nanoparticlesmentioning
confidence: 99%
“…The authors claim that the absorption band of C=O at 1680 cm −1 shows linking of cisplatin with NPs surface, but the absorption of free carboxyl group lies in exactly the same region of 1725 ± 65 cm −1 . So there seems to be a real possibility that cisplatin is simply entangled physically within MHDA (Figure 15) [52,53]. Raman spectra of: cisplatin (black spectrum), the pure MHDA (red spectrum), the Au NPs + MHDA (blue spectrum), Fe 3 O 4 @-SiO 2 @Au + MHDA + cisplatin (green spectrum).…”
Section: Silica-pt(ii) Conjugatesmentioning
confidence: 99%
“…Raman spectra of: cisplatin (black spectrum), the pure MHDA (red spectrum), the Au NPs + MHDA (blue spectrum), Fe 3 O 4 @-SiO 2 @Au + MHDA + cisplatin (green spectrum). There is a mistake in the figure as the value for C=O differs from the one in the text in both papers[52,53].…”
mentioning
confidence: 97%